Tecunumania stothertiae (Cucurbitaceae): a new species from western Ecuador and a new generic record for South America - Cornejo, Xavier; Schaefer, Hanno; Nee, Michael H. (Phytotaxa, 2020)
Tecunumania stothertiae (Cucurbitaceae), a new species of herbaceous vine endemic to western Ecuador, is here described and illustrated. The discovery of Tecunumania stothertiae represents a new generic record for Ecuador and for South America. It represents a new southern extension for Tecunumania, a genus previously thought to be endemic to Mesoamerica. The conservation status of Tecunumania stothertiae is here assessed as Endangered.